2014
DOI: 10.1007/s00018-014-1567-6
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine deprivation initiates reversible assembly of mammalian rods and rings

Abstract: Rods and rings (RR) are protein assemblies composed of cytidine triphosphate synthetase type 1 (CTPS1) and inosine monophosphate dehydrogenase type 2 (IMPDH2), key enzymes in CTP and GTP biosynthesis. Small-molecule inhibitors of CTPS1 or IMPDH2 induce RR assembly in various cancer cell lines within 15 min to hours. Since glutamine is an essential amide nitrogen donor in these nucleotide biosynthetic pathways, glutamine deprivation was examined to determine whether it leads to RR formation. HeLa cells cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 32 publications
8
95
1
Order By: Relevance
“…An emerging theme in RR research is that drugs that throttle GMP biosynthesis, either by directly inhibiting IMPDH (with mycophenolic acid or ribavirin) or indirectly by limiting essential precursor availability (by inhibiting glutamine synthetase with DON or methionine sulfoximine) likewise promote RR assembly (Calise et al, 2014b;Carcamo et al, 2011;Gou et al, 2014;Gunter et al, 2008;Ji et al, 2006). We demonstrated here that RR formation also occurs when cells are treated with methotrexate or aminopterin, which target dihydrofolate reductase.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…An emerging theme in RR research is that drugs that throttle GMP biosynthesis, either by directly inhibiting IMPDH (with mycophenolic acid or ribavirin) or indirectly by limiting essential precursor availability (by inhibiting glutamine synthetase with DON or methionine sulfoximine) likewise promote RR assembly (Calise et al, 2014b;Carcamo et al, 2011;Gou et al, 2014;Gunter et al, 2008;Ji et al, 2006). We demonstrated here that RR formation also occurs when cells are treated with methotrexate or aminopterin, which target dihydrofolate reductase.…”
Section: Discussionmentioning
confidence: 79%
“…Purine and pyrimidine nucleotides are mainly derived from amino acids, and we have demonstrated that depriving cells of glutamine leads to RR formation (Calise et al, 2014b). Moreover, irreversible inhibition of glutamine synthetase by methionine sulfoximine induces RR assembly.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations